Establishing the role of serum cardiac markers in diagnosis of acute chest pain(A Study of 200 cases) - Dr. Sameep Garg; Dr. Mitsu Vaishnav (Tropical Journal of Pathology and Microbiology, 2018)
Introduction:Acute myocardial infarction (AMI) continues to be a major health problem in industrialized and developing countries like India despite progressive research in diagnostic and management over last three decades.AMI has typically been diagnosed on the basis of triad of clinical syndromes of chest pain, electrocardiogram (ECG) changes and elevated serum enzyme activity.Due to high cardiac specificity of ckmb,cTnI, these biomarkers have become the recommended biomarkers for the diagnosis of myocardial injury. Aims:To study changes in serum cardiac markers and determine the sensitivity and specificity of Highly sensitive Troponin I, CK-MB and LDH. Material and Methods:It was undertaken from November-2015 to December-2016 during which 200 patients were studied. All the patients having complaint of acute chest pain admitted in the emergency wards are included. Serum level of cardiac Troponin I was determined by using vidashigh sensitive troponin i (human cardiac specific) enzyme immunoassay kit, CK-MB was determined by the vitros 250 fully automated biochemistry analyser,serum level of LDH was determined by ldh-(p-l) reagent kit (kinatic procedure). Result:In present study, out of 200 patients who admitted for complaining of acute chest pain, 110 patients actually diagnosed to have acute myocardial infarction. Sensitivity and specificity of hsTroponin I for diagnosis of acute myocardial infarction was 100%. CK-MB was 89.1% and 88.8% andLDH was 65.4% and 60% respectively. Conclusion:Among the cardiac markers studied hsTroponin I is the most specific and sensitive for diagnosis of acute myocardial infarction. As CK-MB levels become normal within 2-3 days, it is helpful in diagnosis of reinfarction.